Novel [NF2O]+ and [N3NFO]+-based energetic oxidizers for solid propellants with super high specific impulse. Issue 38 (3rd May 2017) - Yu, Yi; Chen, Jifeng; Zhang, Rubo; Li, Yuchuan; Pang, Siping
Abstract : Novel [NF2 O] + and [N3 NF2 O] + -based energetic oxidizers show super high specific impulses with high thermal stabilities and synthesis possibilities, which may be used as a potential new generation of solid propellants. Abstract : Novel [NF2 O] + and [N3 NFO] + -based energetic oxidizers were designed, and their structures, thermal stabilities, and energetic properties were investigated via density functional theory (DFT). The analysis of the bond dissociation energies (from 93.4 to 120.8 kcal mol −1 ) for the screened salts suggests that they possess better thermal stabilities than the reported [NF2 O] + SbF6 − (89.8 kcal mol −1 ), and compound5 was the most stable energetic salt. All the screened salts possess a positive oxygen balance ranging from 13% to 50%. Due to a positive oxygen balance, the specific impulses of the compounds5, 11–14 (>300 s) were superior to those of ammonium perchlorate (AP) and ammonium dinitramide (ADN) when the optimized ratio of oxidizer/aluminium/PBAN (%) was 76 : 10 : 14. Considering their thermal stability and chemical reactivity, compounds5 and11 with super high specific impulses can be regarded as excellent candidates for novel potential solid propellants.